Correlation between plasmacytoid dendritic cell activation and suppression of subjective physical symptoms following Lactobacillus paragasseri SBT2055 ingestion: a randomized, double-blind, placebo-controlled, parallel-group comparative study - Kobatake, Eiji; Ebihara, Shukuko; Miyoshi, Masaya; Namba, Toshiharu; Arai, Toshinobu (Frontiers in Nutrition, 2026)
ObjectiveThis study examined the relationship between physical condition and plasmacytoid dendritic cell (pDC) activation in healthy adults who ingested Lactobacillus paragasseri SBT2055 (LG2055).MethodsThis randomized, double-blind, placebo-controlled, parallel-group comparative study involved 200 participants who were randomly divided into the LG2055 and placebo groups. The participants ingested one bottle of drinkable yogurt with or without LG2055 daily for 12 weeks. A daily physical health questionnaire on local and systemic symptoms of the common cold was used as the primary outcome. The secondary outcomes were pDC activity, pDC frequency, and IFN-α production by peripheral blood mononuclear cells.ResultsOf the 200 participants, 196 completed the intake, and after excluding 8 participants, 188 (95 in the LG2055 group and 93 in the placebo group) were analyzed. The LG2055 group showed a significantly lower ratio of “with symptoms” during the intake period for nine symptoms (nasal congestion, sneezing, hoarseness, cough, headache, general malaise, chills, feverishness, and feeling unwell) (Chi-squared test, p < 0.05). Based on reports that aging correlates with numerical and functional decline in pDCs, stratified analysis was conducted and revealed that changes in the expression levels of cell surface markers (CD86, HLA-DR, and CD40) in pDCs were significantly higher in the LG2055 group among young participants (<40 years), whereas LG2055 intake suppressed changes in physical condition. In middle-aged participants (≥40 years), LG2055 neither activated pDCs nor strongly influenced their physical condition.ConclusionThe study results indicate that pDC activation by LG2055 contributes to the maintenance of physical condition and suggests that LG2055 improves subjective symptoms by activating pDCs.Clinical trial registrationhttps://www.umin.ac.jp/ctr/index.htm, identifier UMIN000055950.